2012
DOI: 10.1016/j.aquaculture.2010.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aggressive interaction on downstream movement and olfactory function in masu salmon, Oncorhynchus masou

Abstract: In the present study, behavioral, electrophysiological, and molecular biological experiments were developed to examine the role of aggressive interaction ("fighting experience") on downstream movement and olfactory function in relation to smoltification in hatchery-reared one-year-old masu salmon (Oncorhynchus masou). Individual salmon that lost the fighting contest in April and May moved downstream earlier than the winners. The olfactory response to salinity sensitivity of the losers, measured by electro-olfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Taken together, these results may suggest that other intrinsic processes, such as those related to metabolism and energy allocation, may be more important in determining migration timing than smoltification. In another study, Lee & Ueda (2012) found that during the smoltification period, masu salmon ( Oncorhynchus masou ) that lost an aggressive interaction to another individual exerted strong influence on downstream movement and olfactory function. Specifically, less‐aggressive individuals had higher olfactory sensitivity (measured by an electro‐olfactogram) and migrated earlier than more‐aggressive individuals.…”
Section: Physiological Aspects and Their Role In Determining Life‐his...mentioning
confidence: 99%
“…Taken together, these results may suggest that other intrinsic processes, such as those related to metabolism and energy allocation, may be more important in determining migration timing than smoltification. In another study, Lee & Ueda (2012) found that during the smoltification period, masu salmon ( Oncorhynchus masou ) that lost an aggressive interaction to another individual exerted strong influence on downstream movement and olfactory function. Specifically, less‐aggressive individuals had higher olfactory sensitivity (measured by an electro‐olfactogram) and migrated earlier than more‐aggressive individuals.…”
Section: Physiological Aspects and Their Role In Determining Life‐his...mentioning
confidence: 99%